Citation Data and Informetrics Laws: An Application in Doctoral Theses to the Turkish Librarianship - Özlem Gökkurt Bayram (Türk Kütüphaneciliği)
Seventeen doctoral theses of librarianship have been selected to study the application of informetrics laws. Aricles cited in the bibliographies of theses and the journals in which they appeared were entred into a database and synchronic citation analysis has been performed on the data. Journals which contained the cited articles were classified into three groups in accordence with the Bradford law. TKDB / TK was the most heavily used core journal in the doctoral theses of librarianship. Findings suggest that the majority of citations were for relatively older articles and the use of articles was rather low(30 %).